Workshop on Germ Cells - Dosch, Roland (Frontiers in Cell and Developmental Biology, 2018)
Germ cell research in vertebrates has traditionally been challenging, but recent breakthroughs have overcome technical difficulties, demonstrating and expanding the power of the zebrafish experimental system for their analysis in vivo. Exploiting the transparency of the zebrafish embryo, germ cell migration was the first topic that moved the germ cells of this organism into the spotlight of modern research. In recent years however, research on teleost germ cells has expanded into additional fields, manifested by a session dedicated to this cell type at the European Zebrafish PI meeting in Trento.